2008
DOI: 10.3174/ajnr.a1164
|View full text |Cite
|
Sign up to set email alerts
|

No Increased Risk for Contrast-Induced Nephropathy after Multiple CT Perfusion Studies of the Brain with a Nonionic, Dimeric, Iso-Osmolal Contrast Medium

Abstract: BACKGROUND AND PURPOSE: Contrast-induced nephropathy (CIN) is one of the most common causes of in-hospital acute renal failure. The aim of this study was to assess the risk for CIN after repeated administration of the nonionic, dimeric, iso-osmolal contrast agent iodixanol regardless of pre-existing renal function. Changes in serum creatinine (SCr) levels were compared with those of control subjects who did not receive iodinated contrast media (CM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 41 publications
1
29
1
1
Order By: Relevance
“…In addition, it is known that estimated glomerular filtration rate (eGFR) is more accurate than SCr at T he incidence of contrast materialinduced nephrotoxicity (CIN) in the setting of intravenously (IV) administered low-osmolality contrast material (LOCM) (ie, that administered routinely for contrast-enhanced computed tomography [CT] studies) is controversial (1)(2)(3)(4). In recent years, retrospective studies have shown similar rates of post-CT acute kidney injury (AKI) in nonenhanced and contrast-enhanced CT populations (2,(5)(6)(7)(8)(9)(10), which led some to question the incidence of CIN in this setting and whether it occurs at all (3,4). This topic has considerable clinical relevance because concern for renal toxicity is a main reason to avoid IV contrast material in some patients (11)(12)(13)(14)(15).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is known that estimated glomerular filtration rate (eGFR) is more accurate than SCr at T he incidence of contrast materialinduced nephrotoxicity (CIN) in the setting of intravenously (IV) administered low-osmolality contrast material (LOCM) (ie, that administered routinely for contrast-enhanced computed tomography [CT] studies) is controversial (1)(2)(3)(4). In recent years, retrospective studies have shown similar rates of post-CT acute kidney injury (AKI) in nonenhanced and contrast-enhanced CT populations (2,(5)(6)(7)(8)(9)(10), which led some to question the incidence of CIN in this setting and whether it occurs at all (3,4). This topic has considerable clinical relevance because concern for renal toxicity is a main reason to avoid IV contrast material in some patients (11)(12)(13)(14)(15).…”
Section: Subjectsmentioning
confidence: 99%
“…This contributes noise to any CIN analysis, and many patients may be assigned a diagnosis of CIN when other nephrotoxic agents or conditions are to blame (16,17). The nonenhanced CT population has been used as a way to control for baseline post-CT AKI risk (2,(5)(6)(7)(8)(9)(10), but this is insufficient because it does not address the numerous risk factors for CIN (eg, diabetes mellitus or pre-CT AKI), in addition to chronic renal insufficiency, that may cause iodinated contrast material to be withheld. Because a large fraction of patients who are examined with nonenhanced CT have nephrotoxic risk factors that are directly responsible for the clinical avoidance of contrast material, the nonenhanced and contrast-enhanced CT populations are fundamentally different.…”
Section: Subjectsmentioning
confidence: 99%
“…It also has been reported that there was no correlation between the number of contrast-enhanced CT examinations and the incidence of CIN [87]; the incidence of AKI did not differ between patients receiving contrast media twice within 32 h and those receiving no contrast media [93]; and the incidence of CIN did not increase in patients undergoing contrast-enhanced CT followed by CAG [99]. There is no conclusive evidence demonstrating that repeated contrast-enhanced CT increases the risk of CIN.…”
Section: Level Of Evidence: V Grade Of Recommendation: C2 Rationale Cmentioning
confidence: 72%
“…Case series that included only patients undergoing contrast-enhanced CT have reported that baseline kidney dysfunction is a risk factor for CIN [66,[88][89][90][91]. In two cohort studies in which change over time in SCr levels was compared between patients undergoing plain and contrast-enhanced CT examinations, the incidence of an increase in SCr levels did not show statistically significant difference between the 2 groups [92,93].…”
Section: Level Of Evidence: Iva Grade Of Recommendation: B Rationale mentioning
confidence: 99%
“…Case series that included only patients undergoing contrast-enhanced CT have reported that baseline kidney dysfunction is a risk factor for CIN [66,[88][89][90][91]. In two cohort studies in which change over time in SCr levels was compared between patients undergoing plain and contrast-enhanced CT examinations, the incidence of an increase in SCr levels did not show statistically significant difference between the 2 groups [92,93]. Alternatively, it has been widely believed that the risk for developing CIN after CAG or catheterization increases in patients with CKD (see CQ5-1).…”
Section: Level Of Evidence: Iva Grade Of Recommendation: B Rationale mentioning
confidence: 99%